Family farming: a business opportunity - Silva, Fábio José Vieira da (ANAP Brazil, 2025)
The survey shows the panoramic trajectory of family farming, from the perspective of a business that can become promising in the short term. In summary, the economic approaches to the changes that occurred in the economy over time were contemplated and, consequently, culminated in the scenario that provided the creation and expansion of programs that contributed to a positive outcome in favor of the strengthening of the segment. These events generated employment and income and stimulated the local economy, therefore, they also collaborated for regional development. To present the interpreted contexts, documentary and bibliographic research in periodicals, websites and official government platforms, books and an empirical part were used as a methodology. With the information, the findings of the research were demonstrated, which evidenced the reported evidence, exposing the arguments to clarify the problem, that from the economic perspective, family farming is supported by the government, which makes it a business opportunity.